Penalaran Abduktif melalui Literasi Informasi Ilmiah: Pemahaman Siswa tentang Perubahan Iklim di Media Sosial - Nur Rahmah; Supriyatman; Raya Agni; Rahmita; Pahriadi (Jurnal Penelitian Pendidikan IPA, 2025)
Students frequently encounter complex and sometimes misleading climate change information on social media, yet their ability to reason scientifically and evaluate sources remains limited. This study investigates how junior high school students engage in abductive reasoning to interpret such information through the lens of scientific information literacy. A qualitative case study involving eighth-grade students in Central Sulawesi, Indonesia, was conducted using think-aloud interviews, where students analyzed climate change–related social media posts. Thematic analysis mapped reasoning patterns across the exploration, examination, selection, and explanation stages. Findings show that students identified explicit scientific information, but their abductive reasoning was dominated by intuitive, experience-based responses rather than evidence-based reasoning. Their scientific information literacy was limited to basic access and personal verification, while skills in evaluating credibility and disseminating valid information were underdeveloped. The study proposes a conceptual model integrating five dimensions of information literacy with four stages of abductive reasoning to explain how students construct their understanding of climate change. Strengthening literacy can guide reasoning from intuitive to evidence-based explanations. Practically, the findings offer insights for educators and policymakers to design science learning strategies that integrate reasoning and literacy development in digital contexts.